2014
DOI: 10.1037/sgd0000067
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status as context for minority stress and health disparities among lesbian, gay, and bisexual individuals.

Abstract: Despite the robust, graded association between socioeconomic status (SES) and health, SES has largely been ignored in the field of psychology and in lesbian, gay, and bisexual (LGB) health research specifically. This inattention to SES is partly attributable to the “myth of gay affluence” (the assumption that LGB people are wealthier than the general population), which evidence is beginning to disprove. Given that there is no integrated framework for understanding the role of SES in LGB health, this review pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 137 publications
(205 reference statements)
2
42
0
Order By: Relevance
“…In fact, while issues of religion and migration background were identified by some participants, other dimensions were more invisible (sexual orientation, social class and socio‐economic status) in case conceptualisation. This finding strengthens recognition of the need to integrate SES into research on health inequalities, and its interaction with other identity dimensions, as it may be an unexamined fundamental variable (McGarrity, ). In addition, White (heterosexual/lesbian, Christian) clients were rarely perceived as cultural.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In fact, while issues of religion and migration background were identified by some participants, other dimensions were more invisible (sexual orientation, social class and socio‐economic status) in case conceptualisation. This finding strengthens recognition of the need to integrate SES into research on health inequalities, and its interaction with other identity dimensions, as it may be an unexamined fundamental variable (McGarrity, ). In addition, White (heterosexual/lesbian, Christian) clients were rarely perceived as cultural.…”
Section: Discussionsupporting
confidence: 68%
“…Research has begun to explore the role of intersections of social categories, including socio‐economic status and its combination with individual and cultural minorities (e.g. Adler & Stuwart, ; McGarrity, ). Results have suggested the importance of examining health inequalities in the context of socio‐economic status (SES).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual minorities with less education may similarly be exposed to more negative life events and chronic stressors compared to those with higher levels of education. 31 The combined impact of minority stress and other stressors on health is thought to be exacerbated for those with less education and lower socioeconomic status because they are more vulnerable psychologically and physically due to deficiencies in their resources for resilience and a limited capacity to replenish resources for coping with stressful life events, a concept known as the reserve capacity model. 31,32 Findings from this study also suggested that Hispanic sexual minority adults may be more vulnerable to misusing nicotine or other substances in the presence of sexual orientation-based discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…31 The combined impact of minority stress and other stressors on health is thought to be exacerbated for those with less education and lower socioeconomic status because they are more vulnerable psychologically and physically due to deficiencies in their resources for resilience and a limited capacity to replenish resources for coping with stressful life events, a concept known as the reserve capacity model. 31,32 Findings from this study also suggested that Hispanic sexual minority adults may be more vulnerable to misusing nicotine or other substances in the presence of sexual orientation-based discrimination. Recently, Ortiz et al 33 observed that Latino sexual minorities were at increased risk, although nonsignificantly, of smoking compared to other sexual minorities in all of their models; however, they noted an absence of work done to identify reasons for these differences in smoking patterns among sexual minorities.…”
Section: Discussionmentioning
confidence: 99%